2013
DOI: 10.3117/plantroot.7.83
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of nitrogen uptake in oat by cutting hairy vetch grown as an associated crop

Abstract: Legume-grass mixed cropping has significant advantages that affect crop yield and soil resources. Generally, grasses grown with legumes take up more nitrogen than those grown under sole cropping. We focused on the effect of cutting hairy vetch during a vigorous growth stage on N uptake in oat under mixed cropping. We evaluated the amounts of N transferred from hairy vetch to oat by using a 15 N dilution method. Cutting hairy vetch increased the number of tillers and dry weight of oat, but total N content was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…For example, it was found that defoliation of hairy vetch (Vicia villosa Roth.) increased N transfer to oat by 26 % compared to the absence of defoliation in a mixed crop (Tarui et al 2013). Another study which simulated aboveground herbivory showed that shoot removal increased N transfer from white clover to perennial ryegrass (Ayres et al 2007).…”
Section: Defoliation Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it was found that defoliation of hairy vetch (Vicia villosa Roth.) increased N transfer to oat by 26 % compared to the absence of defoliation in a mixed crop (Tarui et al 2013). Another study which simulated aboveground herbivory showed that shoot removal increased N transfer from white clover to perennial ryegrass (Ayres et al 2007).…”
Section: Defoliation Stressmentioning
confidence: 99%
“…Defoliation is the removal of aboveground plant materials, associated with grazing, mowing, frost, insect damage, or herbicide application. Defoliation of legume plants enhances N transfer to neighboring non-legumes (Ayres et al 2007;Tarui et al 2013). Furthermore, the defoliation frequency of the legume has a positive relationship with N transfer rates to companion grasses (Høgh-Jensen and Schjoerring 1994), although other studies contradict these results (Dahlin and Martensson 2008;Dahlin and Stenberg 2010b;Frankow-Lindberg and Dahlin 2013).…”
Section: Defoliation Stressmentioning
confidence: 99%